Urinary Nephrin: A Potential Biomarker of Early Glomerular Injury in a Cohort of Pregnant Women Attending Routine Antenatal Care Services - Belete Biadgo Mesfine; Danica Vojisavljevic; Ranjna Kapoor; David Watson; Yogavijayan Kandasamy; Donna Rudd (International Journal of Nephrology)
Conclusion: The study found that urinary NCR were elevated not only in women with micro- and macroalbuminuria but also in pregnant women with normoalbuminuria. Increased urinary NCR without increased urinary albumin may be associated with early glomerular injury. Urinary NCR may be a more sensitive marker than microalbuminuria to detect early glomerular injury in women with systemic disease and adverse pregnancy outcomes.